2021
DOI: 10.3354/meps13572
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic conditions associated with white shark (Carcharodon carcharias) habitat use along eastern Australia

Abstract: Management of species with wide-ranging migrations is a complex issue, made more challenging when the species is both protected and poses a risk to humans. Understanding the oceanic conditions associated with shark habitat use can help develop mitigation strategies or warning systems that meet both conservation and human safety objectives. Using satellite tracks from 77 juvenile and sub-adult white sharks tagged over 10 yr, we modelled individual movement patterns using hidden Markov models and applied general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 72 publications
(67 reference statements)
5
20
0
Order By: Relevance
“…HMMs are thus advantageous relative to other more conventional techniques (e.g., linear or non-linear modeling) because they provide an objective, data-driven approach to automatically classify behavioral states using remotely collected sensor data and, importantly, can predict how each state shifts through time in response to intrinsic (e.g., biological) or extrinsic (e.g., environmental) factors (Leos-Barajas et al, 2017). Behavioral applications of HMMs have mostly focused on determining animals' foraging patterns and movements, revealing how these are shaped by biological (e.g., age, sex; Grecian et al, 2018;Carter et al, 2020), environmental (e.g., oceanographic features; Byrnes et al, 2021;Lee et al, 2021) and anthropogenic factors (e.g., fishing activity, tourism operations; Towner et al, 2016;Mul et al, 2020). Similarly, combining biologging and HMMs offers a promising framework for better characterizing recovery processes following capture, studying natural behavior and, importantly, distinguishing between the two.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMMs are thus advantageous relative to other more conventional techniques (e.g., linear or non-linear modeling) because they provide an objective, data-driven approach to automatically classify behavioral states using remotely collected sensor data and, importantly, can predict how each state shifts through time in response to intrinsic (e.g., biological) or extrinsic (e.g., environmental) factors (Leos-Barajas et al, 2017). Behavioral applications of HMMs have mostly focused on determining animals' foraging patterns and movements, revealing how these are shaped by biological (e.g., age, sex; Grecian et al, 2018;Carter et al, 2020), environmental (e.g., oceanographic features; Byrnes et al, 2021;Lee et al, 2021) and anthropogenic factors (e.g., fishing activity, tourism operations; Towner et al, 2016;Mul et al, 2020). Similarly, combining biologging and HMMs offers a promising framework for better characterizing recovery processes following capture, studying natural behavior and, importantly, distinguishing between the two.…”
Section: Introductionmentioning
confidence: 99%
“…In New South Wales, Australia, white sharks are caught, relocated ∼1 km offshore, and released through a non-lethal mitigation approach using Shark-Management-Alert-in-Real-Time (SMART) drumlines (Tate et al, 2021a), yet their behavioral responses to capture, and hence the implications of this strategy for both sharks and people, are unknown. Although white sharks' broad scale movements have been the subject of several studies (Jorgensen et al, 2010;Skomal et al, 2017;Spaet et al, 2020a,b;Lee et al, 2021), knowledge of their fine scale behavior remains restricted to a few specific contexts (e.g., foraging near seal colonies; Jewell et al, 2019;Semmens et al, 2019;Watanabe et al, 2019a,b). A more detailed understanding of both their post-capture responses and natural behavior across ecological contexts is thus critical to their management and conservation.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to shorter track durations for other regions (Weng et al, 2007b) or physical and/or biological differences between regions, such as prey availability, predation pressures, or bathymetry (Spaet et al, 2020). In the WNA there is also a consistent shift in increased proportion of time spent in offshore waters (longitudinal expansion) with increasing body size, similar to that observed for the white shark in Australia (Bruce et al, 2019;Lee et al, 2021) and the NEP (Jorgensen et al, 2010;Domeier, 2012;Domeier and Nasby-Lucas, 2012;Hoyos-Padilla et al, 2016). These longitudinal range expansions may reflect a reduction in predation risk after threshold sizes are reached (Skov et al, 2011;Hussey et al, 2017;Stump et al, 2017); improved access to biological or physical features to meet changing physiological demands (food sources, temperature profiles) (Ford, 1983;Breau et al, 2011;Braun et al, 2019); and/or in the case of off-shelf movements, to use alternate migratory pathways that reduce travel time to/from residency areas, or to select or avoid particular features such as the Gulf Stream current or associated habitats (Block et al, 2011;Dodson et al, 2013;Chambault et al, 2017;Gaube et al, 2018).…”
Section: Size/sex Variation In Movementmentioning
confidence: 65%
“…Contemporary research using multiple tag technologies to obtain longer-term datasets has yielded key insights into how aquatic animals interact with their environment (e.g., Vaudo et al, 2017;Braun et al, 2019;Cochran et al, 2019;Hoffmayer et al, 2021), potential drivers of vertical and horizontal movement (e.g., Coffey et al, 2017;Gaube et al, 2018;Lee et al, 2021), and how space use changes through ontogeny (e.g., Skomal et al, 2017;Ajemian et al, 2020), while also providing critical information for the implementation of effective management and conservation strategies (e.g., Acuña-Marrero et al, 2017;White et al, 2017;Bangley et al, 2020). In recent years, studies using pop-up satellite-linked archival tags (PSATs) on sharks have revealed long-term movement and migration routes as well as habitat use patterns (e.g., Weng et al, 2007a,b;Pade et al, 2009;Comfort and Weng, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation